Allylnickel(II) complexes of bulky 5-substituted-2-iminopyrrolyl ligands. (1st October 2021) - Cruz, Tiago F.C.; Lopes, Patrícia S.; Gomes, Pedro T.
Graphical abstract: New η 3 -allyl-Ni(II) complexes of bulky 5-substituted-2-iminopyrrolyl complexes are synthesized and structurally characterized. These complexes undergo a pyridine-assisted cis - trans isomerization process. They act as homogeneous catalysts for the isomerization of hex-1-ene. Highlights: A η 3 -cyclooctenyl-Ni(II) 5-substituted-2-iminopyrrolyl complex is identified. Four new η 3 -allyl-Ni(II) 5-substituted-2-iminopyrrolyl complexes are reported. The η 3 -allyl-Ni(II) complexes undergo pyridine-assisted allyl cis – trans isomerization. The η 3 -allyl-Ni(II) complexes act as hex-1-ene isomerization precatalysts. Abstract: The optimized reaction between [Ni(COD)2 ] (COD = 1, 5-cyclooctadiene) and ligand precursor 5-(2, 4, 6-triisopropylphenyl)-2-[N-(2, 6-diisopropylphenyl)-formimino]- 1H -pyrrole yielded the η 3 -cyclooctenyl-Ni(II) complex [Ni{κ 2 N, N' -5-(2, 4, 6- i Pr3 C6 H2 )-NC4 H2 -2-C(H) = N(2, 6- i Pr2 C6 H3 )}(η 3 -C8 H13 )] 1 . Subsequently, the η 3 -allyl complexes [Ni{κ 2 N, N' -5-R-NC4 H2 -2-C(H)=N(2, 6- i Pr2 C6 H3 )}(η 3 -C3 H5 )] (R = 3, 5-(CF3 )2 C6 H3 (2a ), 2, 6-Me2 C6 H3 (2b ), 2, 4, 6- i Pr3 C6 H2 (2c ) and CPh3 (2d )) were prepared in good yields via metathesis of [Ni(η 3 -C3 H5 )(µ-Br)]2 with the respective potassium 5-R-2-[N-(2, 6-diisopropylphenyl)formimino]pyrrolyl salt (KLa-d ). Complexes 1 and 2a -d were characterized by NMR spectroscopy, elemental analysis and complex 2d further analyzed by single crystal X-ray diffraction. Addition of excess pyridine to solutions of complexes 2a -d led to the observation of a fluxional process that, according to VT-NMR experiments, corresponds to a pyridine-assisted cis – trans isomerization process occurring in these complexes, via a η 3 -η 1 -η 3 haptotropic shift of the allyl ligand, with ΔG ‡ values in range of 9.5–17.3 kcal mol −1 . Additionally, complexes 2a -d, when activated by B(C6 F5 )3, slowly catalyzed the isomerization of hex-1-ene to mixtures of internal olefins.